2006
DOI: 10.1007/s00415-006-7003-6
|View full text |Cite
|
Sign up to set email alerts
|

Dystonia in Parkinson’s disease

Abstract: Dystonia can occasionally be found in idiopathic Parkinson's disease. It is very uncommon in untreated patients and is more frequently seen as a complication of its treatment. In this review, the various types of dystonia occurring in PD, the differential diagnosis with other parkinsonian syndromes associated with dystonia and treatments available are revised. Dystonia unrelated to treatment can be typical (blepharospasm, torticollis), atypical (parkinsonian writer's cramp, camptocormia, anismus), or occurring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
113
0
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(127 citation statements)
references
References 70 publications
2
113
0
7
Order By: Relevance
“…The similarity between the two disorders is underscored by several observations. For instance, it is well known that dystonia occurs in many patients with Parkinson's disease (Tolosa and Compta, 2006), and that the gene defect causing 'DOPA-responsive dystonia' results in prominent Parkinsonism in some individuals (e.g., Van Hove et al, 2006). In addition, electrophysiologic recording studies in dystonic and Parkinsonian patients undergoing neurosurgical procedures have demonstrated similar abnormalities of neuronal firing patterns in the basal ganglia in both dystonia and Parkinsonism (Vitek et al, 1998;Starr et al, 2005), giving rise to the speculation that dystonia, like Parkinsonism, may result from changes in striatal dopaminergic transmission.…”
Section: The Role Of Dopamine In Dystoniamentioning
confidence: 99%
See 1 more Smart Citation
“…The similarity between the two disorders is underscored by several observations. For instance, it is well known that dystonia occurs in many patients with Parkinson's disease (Tolosa and Compta, 2006), and that the gene defect causing 'DOPA-responsive dystonia' results in prominent Parkinsonism in some individuals (e.g., Van Hove et al, 2006). In addition, electrophysiologic recording studies in dystonic and Parkinsonian patients undergoing neurosurgical procedures have demonstrated similar abnormalities of neuronal firing patterns in the basal ganglia in both dystonia and Parkinsonism (Vitek et al, 1998;Starr et al, 2005), giving rise to the speculation that dystonia, like Parkinsonism, may result from changes in striatal dopaminergic transmission.…”
Section: The Role Of Dopamine In Dystoniamentioning
confidence: 99%
“…The age at which a disturbance in dopaminergic metabolism occurs appears to influence the resulting behavioral phenotype (Visser et al, 2000). Spontaneous dystonia in Parkinson's disease occurs predominantly in patients with early-onset disease (Jankovic, 2005;Tolosa and Compta, 2006), and acute dystonic reactions and tardive dystonia in response to neuroleptic medications are more common in children and young adults than in the elderly (Gershanik, 1998). Likewise, among individuals carrying the gene mutation for DOPA-responsive dystonia, childhoodonset disease tends to produce dystonia, while patients with adultonset disease more commonly express Parkinsonism (Bandmann et al, 1996;Uncini et al, 2004).…”
Section: The Role Of Dopamine In Dystoniamentioning
confidence: 99%
“…However, it is known that MS symptoms do not always correlate well with demyelinating plaque location, as shown in patients with MS and cranial nerve palsies (Zadro et al, this issue of CNN) 16 . On the other 8 hand, blepharospasm is also a very rare symptom of PD 17 , and only a minority of patients with idiopathic blepharospasm develop PD 18 . Patients with progressive supranuclear palsy (PSP) are more prone to develop blepharospasm in the course of the illness; however, our patient had no cognitive decline or vertical eye movement paresis, so the diagnosis of PSP was unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately one-third suffer from dystonic movements at some point in their illness, either as a presenting feature or a complication of therapy. 7,8 Thus, it is useful to consider all populations, both primary and secondary, that may benefit from the development of novel therapeutics. If novel therapeutics target both primary and secondary dystonias, they have the potential to benefit large numbers of people.…”
Section: Epidemiology Of the Dystoniasmentioning
confidence: 99%
“…52,53 Dystonia may occur also as an early presenting feature of dopamine neuron loss in Parkinson's disease or as a late consequence of dopaminergic therapies. 7,8 The early and late dystonic manifestations associated with dopamine neuron loss can be replicated in nonhuman primates exposed to 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP).…”
Section: Rational Design: Shared Pathways Strategymentioning
confidence: 99%